The International Plant Diagnostic Network West Africa - Beed, Fenton D.; Sikirou, R.; Bandyopadhyay, Ranajit; Twizeyimana, M.; Miller, S. (2008)
Diseases do not respect national boundaries. The International Plant Diagnostic Network (IPDN) was initiated to improve the capacity for precise and rapid disease diagnostics across West Africa. A disease can only be controlled in an appropriate manner if the causal agent is known. Incorrect diagnosis of disease has led to significant losses in food production which impacts directly on the health and income of farmers. Furthermore, it has impacted on trade opportunities through the accumulation of residues of prohibited pesticides and mycotoxins and the presence of outlawed pathogens. West Africa’s IPDN was established with a hub lab at IITA Bènin with spoke labs in Ghana, Mali and Senegal with support provided by IITA Nigeria. The urgent need for a network such as the IPDN was demonstrated by results from a survey of stakeholders in the region. Furthermore, evidence of the increasing failing capacity of Africa to recognize and hence control current, new and emerging diseases is demonstrated by the fact the number of New Disease Reports (NDR) in Africa have rapidly decreased over the last 100 years while they have rapidly increased in Europe (Foresight 2006: Infectious Diseases: preparing for the future Action Plan). The West African IPDN has initiated a network of experts across the region which has increased awareness of how to diagnose, control and report crop diseases. The IPDN network is being enhanced through the introduction of an internet based communication tool called DDIS (Distance Diagnostic Information System) which will increase linkages to experts within and outside West Africa. DDIS is a tried and tested system that has successfully increased communication to support the National Plant Diagnostic Network in USA.